The Role of the Principal's Leadership in Addressing Students with Problematic Behavior at SMK Bekasi - Bunga Okta Maula Ikami; Puput Novita Sari; Neng Syifa Nurullita; Irnie Victorynie (The Future of Education Journal, 2026)
This study aims to identify the role of the school principal's leadership in addressing students with behavioral issues and to analyze the effectiveness of the implemented policies. The research employed interviews with the principal and teachers at a vocational high school (SMK) in Bekasi. The findings indicate that the principal acts as a manager, a role model, and a facilitator in student guidance. Strategies utilized include the enforcement of school regulations, character building through religious activities, coordination with guidance counselors and homeroom teachers, and collaboration with parents. The effectiveness of these policies is evident in the students' behavioral changes, characterized by increased discipline, politeness, and emotional control. The primary challenges identified are a lack of family attention and the influence of a negative environment.